Teachers’ concepts about playful didactics in technical education integrated to high school - Andreazi, Silvania Gallo; Kobayashi, Maria do Carmo Monteiro (Revista Hipótese, 2022)
This article aimd to identify teachers’ conceptions about the use of playful actions like didactic procedure in Technical Education integrated to High School at Federal Education Institutions. Quali-quantitative and descriptive methods directed to education pointed out as results: research shortage involving playfulness and Technical Education integrated to High School, playful actions protagonists of work’s world situations, gap in the pedagogic training - limiting knowledge and playful attitudes’ purpose in the school context. Generated teaching reflections about its teaching practices expanding knowledge about playful contributions on the education processes.